Un siglo de investigación de la religión en el Perú (Pontificia Universidad Católica del Perú. Fondo Editorial, 1996)
This article tries to present, in its two parts, a thematic-bibliographic balance on the religion of Peru in the 20th century and certain questions that its research has raised today. For this I return to previous works (1983, 1989 and 1995), although now insisting more on the questions. I call religion, based on Durkheim (1912) and Geertz (1965), the system of beliefs, rites, feelings, forms of organization and ethical norms about the divine, which generate certain attitudes and states of mind in the individual and serve to give transcendent meaning to life. However, most of the works reviewed here insist more on the objective dimension than on the subjective dimension of religion; In addition, I exclude from this review books of theology and history of the Church and only exceptionally do I refer to articles, with which my bibliographic universe is smaller than that of Rivera (1985). Este trabajo trata de presentar, en sus dos partes, un balance temático-bibliográfico sobre la religión del Perú en el siglo XX y ciertas preguntas que la investigación de la misma ha planteado hoy. Así retomo trabajos anteriores (1983, 1989 y 1995), aunque ahora insisto más en las preguntas. Llamo religión, partiendo de Durkheim (1912) y Geertz (1965), al sistema de creencias, ritos, sentimientos, formas de organización y normas éticas sobre lo divino, que generan ciertas actitudes y estados de ánimo en el individuo y sirven para dar sentido trascendente a la vida. Sin embargo, la mayoría de los trabajos aquí reseñados insisten más en la dimensión objetiva que en la subjetiva de la religión; además, excluyo de esta reseña los libros de teología e historia de la Iglesia y sólo excepcionalmente me refiero a artículos, con lo que mi universo bibliográfico es más reducido que el de Rivera (1985).